Analysis of Determinants of Firm Value - Luddiana, Yuni Serli; Mujiyati, M (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
The value of the company is one of the most interesting concerns for investors, because the information presented about the value of the company is very diverse, so research on the value of the company always attracts the attention of researchers. This study aims to analyze the determinants of firm value, namely the effect of tax avoidance, leverage, liquidity, activity ratios, and information transparency on firm value. This study uses a sample of infrastructure, utilities, and transportation companies listed on the IDX for the period 2016 to 2020. The sampling technique uses purposive sampling. Based on the sample criteria, a sample of 40 companies was obtained. To analyze the data using multiple linear regression analysis tools. The results showed that the tax avoidance variable had an effect on firm value, while the leverage, liquidity, activity ratio, and information transparency variables had no effect on firm value.